Conceptual Design of Dosing System for Liquids on the Basis of a Robotic Injection Installation Using Interchangeable Capillaries - V.V, Moroz; O.A, A.Kazachkova; L.V, Baulina (International Journal of Engineering and Technology, 2018)
.